Tracing anthropogenic indicators for small-scale land use on the Åland Islands: palynological and correlation analyses - Larsson, Petter I.; Ekblom, Anneli; Ilves, Kristin (Frontiers in Environmental Archaeology, 2025)
This study was undertaken to address the question on anthropogenic landscape modification and how to use such signals within palynology. Pollen, spores, and microscopic charcoal from Lake Dalsträsk in the northern Åland Islands are analyzed, covering the period from 741 BCE (Late Bronze Age) to the early twentieth century. Percentage and influx data are compared as a means of disentangling different land use practices. The results of the palynological analysis are further explored through correlation analysis of influx data and Relative Pollen Productivity (RPP) values. Our findings confirm the presence of modest cereal cultivation and grazing activities from the beginning of the Late Bronze Age a hypothesis that has previously been debated. The study also shows variations in land use after the Bronze Age, with an increase in farming from around 398 CE (Migration Period) and an intensification of grazing activities around 823 CE (Viking Age). Our study shows how land use practices have shifted over the centuries and how these shifts have modified taxa composition. Commonly used 'anthropogenic indicator' pollen taxa show weak or indirect correlations with cereal cultivation and grazing, while some taxa display positive correlations. Our results point to the need to refine the use of anthropogenic taxa in a local context to better elucidate small-scale land use.